Exploring the Digital Transformation of Physical Education: User Perceptions and Supporting Resources - Ramli, Abdul Malik; Ikhsan, Andi; Saleh, Syahruddin (International Journal of Technology and Education Research, 2025)
This study aims to analyze the perceptions of lecturers and students regarding the ease of use of digital platforms in the teaching of Physical Education, Sports, and Health (PJOK). The study is motivated by the growing utilization of digital technology in higher education, particularly in the post-pandemic era that has accelerated the adoption of online and hybrid learning systems. A descriptive quantitative approach was employed, with data collected through questionnaires distributed to respondents who had experience using platforms such as LMS, Zoom, and Google Classroom. The findings reveal that the majority of respondents rated digital platforms as “very easy” (53%) and “easy” (40.9%) to use in PJOK learning activities. However, 12.1% of respondents reported experiencing difficulties, which may be attributed to limited digital literacy, technical barriers, or a mismatch between platform features and the practical nature of PJOK instruction. These findings suggest that although the digitalization of PJOK learning has progressed positively, strategic interventions are still needed, including technical training, device support, and the development of adaptive digital learning models, to ensure that the digital transformation process is inclusive, effective, and sustainable.